The relationship between workplace spirituality and organisational health in an Islamic context - Tlemissov, Ulan (HTS teologiese studies, 2021)
It is widely accepted that some characteristics and aspects of spirituality have been mentioned in the religious beliefs, teachings and practices of many divine (Abrahamic) religions, including Islam. This has recently drawn researchers’ attention, working in the fields of psychology and religion, towards the relationship between religion and spirituality. At present, research on industrial and organisational psychology seeks to shed light on the relationship between religiosity, intelligence and cognitive abilities. In addition, a healthy organisation is a place where individuals attend their workplace with interest and are proud to work there. In fact, a healthy organisation can be achieved with regard to physical–mental health, security, belongings, meritocracy and the valuation of knowledge and expertise. Considering the significance of this study, it aimed to reflect on the relationship between workplace spirituality (WPS) and organisational health (OH) in manufacturing and service companies in Malaysia. Hence, a total number of 30 trading companies in Kuala Lumpur, Penang and Langkawi were selected as the statistical population of the study and 3820 employees in these organisations were investigated by simple random sampling through questionnaires distributed to collect the data required for analysis in SPSS software. The results revealed that the given organisations had good levels of spirituality and health. Accordingly, it was concluded that WPS had a significant positive effect on OH (p = 0.74).Contribution: This article contributes to the relationship between WPS and OH in manufacturing companies.